A GSH/CB Dual-Controlled Self-Assembled Nanomedicine for High-Efficacy Doxorubicin-Resistant Breast Cancer Therapy - Yang, Yang; Zhao, Quanfeng; Peng, Zhe; Zhou, Yunjiang; Niu, Miao-Miao; Chen, Lin (Frontiers in Pharmacology, 2022)
Chemoresistance is a major therapeutic obstacle in the treatment of breast cancer. Therefore, how to overcome chemoresistance is a problem to be solved. Here, a glutathione (GSH)/cathepsin B (CB) dual-controlled nanomedicine formed by cyclic disulfide-bridged peptide (cyclic-1a) as a potent anticancer agent is reported. Under the sequential treatment of GSH and CB, cyclic-1a can efficiently self-assemble into nanofibers. In vitro studies show that cyclic-1a promotes the apoptosis of MCF-7/DOX cells by inducing the cleavages of caspase-3 and PARP. In vivo studies confirm that cyclic-1a significantly inhibits the progression of MCF-7/DOX cells-derived xenograft in nude mice, with no obvious adverse reactions. This study provides a paradigm of GSH/CB dual-controlled nanomedicine for high-efficacy and low-toxic DOX-resistant breast cancer therapy.